Analisis Strategi Pemasaran dalam Meningkatkan Penjualan Pada Bengkel Sahabat Motor - Sukma, Ajeung Dwi Febian; Rinaldi, Aris (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Marketing strategy plays a vital role in increasing sales and ensuring business continuity, especially in service industries such as automotive repair. This study aims to analyze the marketing strategies applied by Bengkel Sahabat Motor to boost its sales performance. A qualitative descriptive method was employed, with data collected through observation, interviews with the owner, mechanics, cashier, and customers, and documentation. The results indicate that the workshop implements a marketing mix strategy (7Ps), including product, price, place, promotion, people, process, and physical evidence. It offers quality services at competitive prices and benefits from a strategic location. Promotions are conducted through social media and discount programs. Friendly and professional service also contributes to customer satisfaction. However, challenges remain, such as limited parking space, price competition, and suboptimal inventory management. In conclusion, the implemented marketing strategies have positively influenced customer growth, loyalty, and overall sales. It is recommended that the workshop enhance its digital marketing efforts, expand its promotional reach, and improve operational efficiency.